Porous spheres assembled from polythiophene (PTh)-coated ultrathin MnO2 nanosheets with enhanced lithium storage capabilities - Xiao, Wei (2012)
In this work, we propose a strategy to enhance the lithium storage capabilities of metal oxide based anodes